Perspectives of psoriasis patients in Turkey - Muhterem Polat; Başak Yalçın; Nuran Allı (Wolters Kluwer Medknow Publications, 2012)
Background: Psoriasis is a chronic skin disease that can have severe psychosocial effects. The aim of this study was to assess the perspectives of psoriasis patients regarding their illness. Methods: One hundred and ten psoriasis patients in the 18-65 age group were included. Data were collected via a "face to face interview" method. The questionnaire included mainly three topics (socio-demographic characteristics of patients; self-evaluations of patients about their disease; knowledge and attitudes about psoriasis). Results: The majority of the patients stated that psoriasis as a socially troubling disease. Almost half of them believed that "stress and unhappiness" was a predisposing factor of their illness. Belief that the occurrence of the disease was due to a contagious infectious agent was the second most frequent factor that patients emphasized. "Signs and symptoms of psoriasis" was the most frequent difficulty patients faced because of psoriasis. Most of the patients who still have their parents, those who have a closest friend in life, and more than half of the patients who have their closest friend at work all stated that there was a change in social relations, mostly arising from their counterparts. More than half of the married patients stated that there was a change in social relations, mostly arising from their spouses. Conclusion: Psoriasis is more than a cosmetic nuisance and can be associated with psychosocial effects that seriously affect patients' lives and social relations. Increasing the patients' knowledge of the disease could have a positive effect on the relations the psoriasis patients have within their social environment.